HPTLC method development and validation of Cefepime and Tazobactam in combined parenteral dosage form - HARISH KUMAR.D.R,; SUMA.B.V,; ABHILASH.B.HIREMATH,; VIJAYBHANU.P,; C.H.S.VENKATARAMANA, (International Journal of Pharma and Bio Sciences, 2018)
To develop a simple, precise, specific, accurate and economical High Performance Thin Layer Chromatographic (HPTLC) method for the simultaneous estimation of Cefepime (CEF) and Tazobactam (TAZ) in combined parenteral dosage form. The method employed HPTLC aluminium plates pre-coated with silica gel 60 F254 as the stationary phase. The mobile phase used was in the combination of chloroform: methanol: water: acetic acid (6:3:1:0.1v/v) and the ratio was foundto give good compact spots for CEF and TAZ. Densitometric analysis was carried out at 254 nm. The Rf value of CEF and TAZ was found to be 0.22 & 0.59 respectively. The regression coefficient for CEF and TAZ were found to be 0.9986 and 0.9978. The linearity was found to be in the range of 2-10 µg/spot and 10-18 µg/spot for CEF and TAZ respectively. RSD was found less than 2%. The percentage recovery was found to be in the range of 98-102%. The method was validated with respect to specificity, linearity, accuracy, precision, limit of detection, limit of quantification and robustness as per ICH guidelines. The method was found to be simple, precise, specific, accurate, robust and economical for the simultaneous estimation and can be used for qualitative and quantitative analysis of CEF and TAZ in bulk and combined parenteral dosage form.